Meeting 24-h movement guidelines and markers of adiposity in adults from eight Latin America countries: the ELANS study - Ferrari, Gerson (2022)
This study aimed to compare compliance with 24-h movement guidelines across countries and examine the associations with markers of adiposity in adults from eight Latin American countries. The sample consisted of 2338 adults aged 18–65 years. Moderate-to-vigorous physical activity (MVPA) and sedentary behavior (SB) data were objectively measured using accelerometers. Sleep duration was self-reported using a daily log. Body mass index and waist circumference were assessed as markers of adiposity. Meeting the 24-h movement guidelines was defined as ≥ 150 min/week of MVPA; ≤ 8 h/day of SB; and between 7 and 9 h/day of sleep. The number of guidelines being met was 0.90 (95% CI 0.86, 0.93) with higher value in men than women. We found differences between countries. Meeting two and three movement guidelines was associated with overweight/obesity (OR: 0.75, 95% CI 0.58, 0.97 and OR: 0.69, 95% CI 0.51, 0.85, respectively) and high waist circumference (OR: 0.74, 95% CI 0.56, 0.97 and OR: 0.77, 95% CI 0.62, 0.96). Meeting MVPA and SB recommendations were related to reduced adiposity markers but only in men. Future research is needed to gain insights into the directionality of the associations between 24-h movement guidelines compliance and markers of adiposity but also the mechanisms underlying explaining differences between men and women.